Case Report: A tortuous diagnosis and successful multimodal treatment of thyroid follicular carcinoma with pelvic metastasis - Hong, Zhi-Liang; Huang, Hai-Jian; Chen, Sheng; Yang, Jian-Chuan; Wu, Song-Song (Frontiers in Oncology, 2023)
Purpose: To provide reference method for the treatment of thyroid follicular carcinoma by studing the clinical imaging, pathological features and multimodal treatment of a case of thyroid follicular carcinoma with bone metastasis. Methods: By identifying the case’s clinical, imaging, pathological features of a case of thyroid follicular carcinoma with bone metastasis, reflecting on the case’s diagnosis and treatment process, and referring to literature about the characteristics of thyroid follicular carcinoma , the study aims to provide reference for the treatment of this kind of disease. Result: A 67-year-old male patient was admitted to the hospital with clinical symptoms of left pelvic pain. The biopsy pathology showed well-differentiated thyroid tissue. Considering his medical history, conclusion of thyroid follicular carcinoma metastasis could be made. Conclusions: Thyroid follicular carcinoma bone metastases are rare. Clinical imaging and pathology are needed for correct diagnosis, and a successful treatment requires a combination of multiple approaches including 131I, local therapy and targeted drug therapy.